Exploring Perceptions and Elements of Entrepreneurial Behavior in Pesantren: Understanding Fundamental Concepts of Entrepreneurial Behavior - Diana, Ilfi Nur; Segaf, Segaf (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2023)
This study aims to analyze the perceptions of understanding, elements, and categories of entrepreneurial behavior important for understanding the basic concepts of Islamic boarding schools' entrepreneurial behavior. This study uses a qualitative approach. The setting of this research is the Riyadlul Jannah Islamic Boarding School because of its uniqueness in developing entrepreneurial behavior. The research design used is a single case study with one unit of analysis, namely members of the pesantren. Key informants were determined purposively, starting from the Board of Trustees of the Islamic Boarding School (Kyai), followed by a snowball method until it reached 30 informants. The research findings show that understanding the meaning of entrepreneurial behavior includes attitudes, lifestyle, and self-confidence to produce economic values that encourage independence. Entrepreneurial behavior includes a series of good deeds (al-amal al-shalih) and noble standards (al-akhlaq al-karimah). The entrepreneurial behavior category consists of personal entrepreneurial behavior, social entrepreneurial behavior, and spiritual entrepreneurial behavior. The basic understanding of Islamic boarding schools' entrepreneurial behavior should be comprehensive, covering all three, namely understanding the meaning, elements, and categories of entrepreneurial behavior.